Non-transecting anastomotic augmentation (Joshi step) BMG ureteroplasty in near obliterative ureteric stricture using robot - Sanjay Kulkarni; Amit Hosamani; Uday Chandankhede; Pankaj Joshi (Urology Video Journal)
NA